1989
DOI: 10.1128/mcb.9.9.4018
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei: posttranscriptional control of the variable surface glycoprotein gene expression site.

Abstract: The arrest of variable surface glycoprotein (VSG) synthesis is one of the first events accompanying the differentiation of Trypanosoma brucei bloodstream forms into procyclic forms, which are characteristic of the insect vector. This is because of a very fast inhibition of VSG gene transcription which occurs as soon as the temperature is lowered. We report that this effect is probably not controlled at the level of transcription initiation, since the beginning of the VSG gene expression site, about 45 kilobase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
42
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 21 publications
8
42
0
1
Order By: Relevance
“…Previous experiments pointed to mixed conclusions. On the one hand, transcripts from inactive ESs could be detected in bloodstream clones and even in procyclic forms, which do not express VSG, suggesting that transcription initiation takes place in all ESs simultaneously (22)(23)(24)(25)(26)(27)(28)(29). On the other hand, experiments tagging ESs with antibiotic-resistance genes showed that RNA expression can be detected from two ES, although the expression was unstable (30).…”
mentioning
confidence: 98%
“…Previous experiments pointed to mixed conclusions. On the one hand, transcripts from inactive ESs could be detected in bloodstream clones and even in procyclic forms, which do not express VSG, suggesting that transcription initiation takes place in all ESs simultaneously (22)(23)(24)(25)(26)(27)(28)(29). On the other hand, experiments tagging ESs with antibiotic-resistance genes showed that RNA expression can be detected from two ES, although the expression was unstable (30).…”
mentioning
confidence: 98%
“…posttranscriptional level. We have found that both transcription promoters are active in the two parasite forms and that differential gene expression is achieved through modification of RNA elongation and stability (7,12,23,24). However, this has not been found by others for the procyclin gene promoter (19,30).…”
mentioning
confidence: 82%
“…brucei bloodstream forms were from the AnTat 1.3A clone, and procyclic forms were derived from the AnTat 1.1B clone by in vitro transformation (23).…”
Section: Methodsmentioning
confidence: 99%
“…This control may include regulated expression from a single promoter or posttranscriptional control. Such posttranscriptional control has been suggested for phosphoglycerate kinase genes (14), the variable glycoprotein expression site (29), and aldolase genes (40) and may include differential processing (miniexon addition or polyadenylation) or inherent stabilities of the mature mRNAs.…”
Section: Discussionmentioning
confidence: 99%